2021
DOI: 10.3390/jcm10163692
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ABO Blood Type on Developing Venous Thromboembolism in Cancer Patients: Systematic Review and Meta-Analysis

Abstract: The impact of ABO blood type in the development of venous thromboembolism in cancer patients remains controversial. To develop a sense of the current opinion in this area, we conducted a systematic review and meta-analysis. In March 2021, we performed a systematic search of PubMed, the Cochrane library, and Scopus for studies that compared cancer patients who had a blood type of either O or non-O (A, B, and AB). Our objective was to use multivariate logistic regression analysis to determine how ABO blood type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our finding of increased VTE risk in patients with a non-O blood type was reported in three previous meta-analyses, one including all cancer studies (including pediatric and leukemia patients), and the others including various patient populations. In these metaanalyses, non-O blood type was significantly associated with VTE, with ORs ranging from 1.74 to 2.09, [58][59][60] thereby closely aligning with our OR of 1.56. The magnitude of our association is slightly smaller than the other studies, but the significant heterogeneity observed in the other two meta-analyses provides evidence that the risk may vary in different patient populations.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding of increased VTE risk in patients with a non-O blood type was reported in three previous meta-analyses, one including all cancer studies (including pediatric and leukemia patients), and the others including various patient populations. In these metaanalyses, non-O blood type was significantly associated with VTE, with ORs ranging from 1.74 to 2.09, [58][59][60] thereby closely aligning with our OR of 1.56. The magnitude of our association is slightly smaller than the other studies, but the significant heterogeneity observed in the other two meta-analyses provides evidence that the risk may vary in different patient populations.…”
Section: Discussionsupporting
confidence: 85%
“…►Table 1 shows the major data extracted from the nine studies resulting from this search. Many of the studies 8,26,[28][29][30][31] highlight a positive association between non-O blood groups and VTE. Thrombotic events were either DVT or PE and almost all studies have reported elevated VWF levels in patients with non-O groups.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it will also be useful to investigate the impact of specific cancer types and patients' risk factors (e.g., tumor stage, tumor size, tumor site, obesity, chemotherapy) as the main drivers for increased risk in light of patients' ABO types. 29 These studies shall help assess the value of ABO as an added biomarker to improve the application of Khorana score or its modifications for better care of this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schleef et al (37) showed that vWF levels in the O-group population ranged from 654 to 1,028 U/L, whereas in the non-O-group population, their vWF levels ranged from 900 to 1,390 U/L, with a mean level of 1,339 U/L. Plasma vWF and circulating factor VIII concentrations are approximately 25% higher in non-O patients than in O patients (38). vWF is a multimer of variable molecular weight secreted by endothelial cells and megakaryocytes (39).…”
Section: Discussionmentioning
confidence: 99%